2013
DOI: 10.1093/toxsci/kft197
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification of Clinically Relevant Drug Interactions With the Human Bile Salt Export Pump (BSEP/ABCB11)

Abstract: A comprehensive analysis was performed to investigate how inhibition of the human bile salt export pump (BSEP/ABCB11) relates to clinically observed drug-induced liver injury (DILI). Inhibition of taurocholate (TA) transport was investigated in BSEP membrane vesicles for a data set of 250 compounds, and 86 BSEP inhibitors were identified. Structure-activity modeling identified BSEP inhibition to correlate strongly with compound lipophilicity, whereas positive molecular charge was associated with a lack of inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
156
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(167 citation statements)
references
References 39 publications
9
156
2
Order By: Relevance
“…2012; Pedersen et al. 2013). Thus, these investigations suggest that cyclosporin‐induced impairment of bile acid efflux and cholestasis could be secondary to ER stress only for high concentrations of this immunosuppressant.…”
Section: Introductionmentioning
confidence: 99%
“…2012; Pedersen et al. 2013). Thus, these investigations suggest that cyclosporin‐induced impairment of bile acid efflux and cholestasis could be secondary to ER stress only for high concentrations of this immunosuppressant.…”
Section: Introductionmentioning
confidence: 99%
“…Their best model reached an accuracy of 0.87 (on a test set of 187 compounds). Finally, Pedersen and colleagues 10 built two orthogonal partial least-squares discriminant analysis (OPLS-DA) models on 163 compounds. They report an accuracy of 0.89 on a test set of randomly selected 86 compounds.…”
mentioning
confidence: 99%
“…Thus, drugs with the potential to inhibit these transporters can disturb the disposition of both co-administered drugs and bile acid, contributing to the development of cholestatic drug-induced liver injury (DILI) [42,43]. In vitro studies with isolated membrane vesicles have demonstrated an association between DILI and the inhibitory effects of drugs on bile acid efflux transporters [43][44][45]. In vitro findings may not translate directly to in vivo hepatotoxicity risk for various reasons, including complexity of bile acid homeostasis, feedback regulation of bile acid synthesis and transport, and dynamic drug/metabolite concentrations in the system [46,47].…”
Section: Pbpk For the Prediction Of Transporter-mediated Drug Inducedmentioning
confidence: 99%